(3bjO GdChGHO ef GdahGFOs - (3CHh GdaVd CMeO Hf eMeO GdeOGfj GdfjSGHhQjs
(3ChdgG (B:s
(3bGd GdEeGe CHh GdaVd CMeO Hf eMeO GdejOGfi gPg MQha MUd di YdjgG hbha Mjf WGdYJ cJGH GdJgPjH ddCRgQi ahLOJ ajg eG jNGda cJGH GdUMGM ddLhgQi s
(3BNQgG (B:s
(3hGdjefi ebUhO JQaC ajg GdSaf jcJH HGdjGA hGddg CYde s
(3GdfSNI HgG MhGTs
(3hgh eG GNJda ajg cJGH GdUMGM ai GddZI hcJGH GdJgPjH ai GddZI ddCRgQis
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3CdeGfjG s
Keywords: (3GdMOjK h GdeUWdMs